Performa Pertumbuhan Strain Ikan Nila (Oreochromis niloticus) Yang Berbeda Pada Sistem Budidaya Minapadi - Salsabila, Alifia; Basuki, Fajar; Hastuti, Sri (Journal of Aquaculture Management and Technology, 2013)
The purpose of study is to observe the effect of different tilapia strains in Rice-fish culture systems to the growth (individual absolute weight growth, RGR), feed utilization eficiency (EPP) and survival rate (SR) of tilapia. The method used in this research was experimental method carried out in the field. The material that used was tilapia seed in size 7 -10 cm with average individual weight 12- 24 gr. The trial design in this research used completely randomized design (CMD) with 3 treatment and 3 replications. The treatment tested A (Larasati), B ( Gift), and C (Gesit). The feed was given 2 times a day in the morning and afternoon. The variable measurable were individual absolute weight growth, RGR, EPP and SR. The result shows that the giving growth performance of different tilapia strains has highly significant (P> 0.01) to the individual absolute weight growth (gr), relatif growth rate (RGR), feed utization eficiency (EPP) and not significant influence (P Ëƒ 0.05) to survival rate (SR) of tilapia. Treatment A gives high relative growth rate and individual absolute weigth growth is 8.81% / day and 125.47 gr. Treatment A provide the best feed utilization eficiency of 84.08% and survival rate ranged from 86.46 to 94.94%. Range of water quality is still in decent condition for tilapia cultivation media. Based on the study it can be concluded that larasati tilapia strain provides the best growth in Rice-fish culture systems.